A cross-sectional study about knowledge and attitudes toward multidrug-resistant and extensively drug-resistant tuberculosis in a high-burden drug-resistant country. Issue 2 (June 2016) - Javed, Hasnain; Tahir, Zarfishan; Hashmi, Hafiza Jawairia; Jamil, Nazia
Abstract: Objective/Background: Tuberculosis (TB) is a leading cause of death worldwide, with new threats of multidrug-resistant (MDR) and extensively drug-resistant (XDR) TB. Pakistan is the fifth highest among high-burden TB countries and the fourth highest among high-burden drug-resistant-TB countries. Pakistan is the sixth most populous country in the world, and Pakistani youth is the highest population group in Pakistan and second in the world. This study was aimed at assessing the understanding, awareness, and mindset of university students toward TB, MDR TB, and XDR TB in Lahore. Methods: A cross-sectional questionnaire-based study was performed on 1137 individuals from three major public-sector universities in Lahore, Pakistan. Information regarding their knowledge and attitude toward MDR and XDR TB was gathered using a structured questionnaire. Data collected was analyzed using SPSS version 20. Results: Male (531) and female (606) students were asked about different aspects of MDR and XDR TB. Although 80.47% students had good knowledge about simple TB, a very small fraction had awareness and appropriate knowledge about MDR/XDR-TB. Considering TB as a stigma, only 9.3% students disclosed that they had household TB contact. Only 25% students knew about XDR TB. Conclusion: Our results indicated that a small fraction of people knew the exact definition and treatment duration of MDR TB and XDR TB in our society. There is a need to increase the awareness and knowledge status of university students about MDR and XDR TB.